Pengaruh Zakat dan Islamic Human Development Index terhadap Kemiskinan di Jawa Tengah Tahun 2017–2020 - Asep Nurhalim; Lelly Mawarni; Resfa Fitri (Department of Islamic Economics, IPB University, 2022)
Human development and zakat funds are one of the efforts to minimize poverty. Human development can be measured using the Islamic Human Development Index (IHDI) indicator for countries or regions with a majority Muslim population. However, there is not much literature on IHDI and its application in Indonesia. This study aims to analyze the effect of zakat and IHDI on poverty in 35 districts/cities of Central Java in 2017–2020. The method used is panel data regression with random effect model estimation. The regression results show that zakat has a negative and significant effect on the poverty level in Central Java in 2017–2020, while IHDI has a negative but not significant effect. Simultaneously, zakat and IHDI have an influence on the poverty rate in Central Java in 2017–2020. One of the policy implications that can be done by the Central Java government to minimize the level of poverty is to increase the realization of the collection and distribution of zakat funds and cooperation from all related parties is also very necessary, including the government, zakat management institutions, banks, and the community.